General types of idiomatic verbal units in English and Swahili - L A Semenkova (Russian journal of linguistics: Vestnik RUDN, 2012)
The article deals with the comparative analysis of the idiomatic verbal units-word combination of the two typologically different languages - English and Swahili: As a result a number of general syntactic types of their idiomatic verbal units are determined.